Tecnoestrés y técnicas cognitivo-conductuales para docentes. Universidad Nacional de Chimborazo, 2020. - Granda Zambrano, Lisbeth Estefania (2021)
ABSTRACT: This study aims to analyze techno-stress and establish cognitive-behavioral techniques for the Faculty of Health Sciences teachers of the National University of Chimborazo, 2020. This research is field and bibliographic, with a non-experimental cross-sectional design at the descriptive level, made up of a sample of 101 teachers selected through a non-probabilistic convenience sampling. The RED-TIC techno-stress questionnaire was applied, which determines the level of technological stress and the dimensions affected. The main results obtained are 61.4% corresponds to deficient and low levels of techno- stress. Concerning the affective proportion, 53.5% are in secondary and low levels of anxiety. Fatigue 41, 6% with high and very high levels, in the attitudinal dimension 56.4% are in deficient and low levels of skepticism. Finally, in the cognitive proportion, 62.3% are located at insufficient levels and low inefficiency. The researchers selected cognitive- behavioral techniques that are adequate to reduce the symptoms caused by techno-stress, ensuring that the teaching staff can self-apply them without forgetting that their effectiveness will increase when applied by a mental health professional.